Religion in the ranks : belief and religious experience in the Canadian Forces - Benham Rennick, Joanne, 1970- (University of Toronto Press, 2011)
"What role does religion play in the Canadian Forces today? Examining the changing functions of the official religious leaders in the chaplaincy as well as the place and purpose of religion in the lives of regular military personnel, Religion in the Ranks explores this question in the context of late modernity and the Canadian secular state. In-depth interviews with chaplains and with personnel of differing spiritual beliefs offer insight into how religion affects the real life experiences of those who have endured difficult assignments, witnessed atrocities, and struggled to overcome post-traumatic stress disorder. While identifying the historic function of religion in the Canadian Forces, Joanne Benham Rennick demonstrates that spiritual interests remain important, even to those who do not consider themselves to be religious. Arguing that the leadership, practices, and beliefs rooted in religious affiliations create essential support systems for individuals, both at home and on assignment, Benham Rennick shows that there is still a place for religion in Canada's military."--Pub. desc.